2011
DOI: 10.1536/ihj.52.32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles, Efficacy of Antiarrhythmic Drug Therapy, and Cardiovascular Prognosis in Patients With First Detected Paroxysmal Atrial Fibrillation

Abstract: SummaryLittle information is available concerning clinical profiles and outcomes of treatment in Japanese patients with first detected atrial fibrillation (AF). In the present study, 459 patients with paroxysmal AF (309 males, mean age, 66 ± 12 years) were divided into a first detected AF group (group A, n = 143) and a non-first detected AF group (group B, n = 316). Clinical profiles, prophylactic efficacy of antiarrhythmic drug therapy (AAD), and cardiovascular prognosis during a mean follow-up period of 50 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A meta-analysis of a large-scale multicenter comparative study (AFFIRM) in a Western country showed that AF type (paroxysmal or persistent) did not significantly affect cardiovascular prognosis for each AF patient, while independent predictors were factors including age, diabetes, underlying heart disease, complications involving heart failure or ischemic stroke, sinus rhythm maintenance, and warfarinbased anticoagulation therapy [29]. We reported that in a follow-up of patients for about 50 months, left ventricular ejection fraction, conversion to permanent AF, and anticoagulation therapy are independent predictors of cardiovascular prognosis following antiarrhythmic drug therapy in patients with AF [30]. However, research remains inadequate on the indicators that may be used to assess prognosis more conveniently.…”
Section: Cha 2 Ds 2 -Vasc Scores For Risk Stratification Of Cardiovasmentioning
confidence: 99%
“…A meta-analysis of a large-scale multicenter comparative study (AFFIRM) in a Western country showed that AF type (paroxysmal or persistent) did not significantly affect cardiovascular prognosis for each AF patient, while independent predictors were factors including age, diabetes, underlying heart disease, complications involving heart failure or ischemic stroke, sinus rhythm maintenance, and warfarinbased anticoagulation therapy [29]. We reported that in a follow-up of patients for about 50 months, left ventricular ejection fraction, conversion to permanent AF, and anticoagulation therapy are independent predictors of cardiovascular prognosis following antiarrhythmic drug therapy in patients with AF [30]. However, research remains inadequate on the indicators that may be used to assess prognosis more conveniently.…”
Section: Cha 2 Ds 2 -Vasc Scores For Risk Stratification Of Cardiovasmentioning
confidence: 99%
“…The mortality rate among AF patients with congestive heart failure 1 year after initial diagnosis is relatively high, between 13% and 20% in Western and countries including the United States [51,52] and 7.3% in Japan [53]. In data from our institute [54], the incidence of new-onset CHF at 1 year in Japanese patients with paroxysmal AF receiving rhythm control therapy was nearly 1.0-2.0%, and the independent predictors of hospitalization for CHF were CHADS 2 score, left ventricular ejection fraction, and underlying heart disease ( Table 5). When cardiovascular events included the composite of hospitalization for thromboembolism, heart failure, and cardiovascular death, the independent predictors of cardiovascular events in Japanese patients with paroxysmal AF receiving rhythm control therapy were also CHADS 2 score, underlying heart disease, left ventricular ejection fraction, conversion to persistent AF, and anticoagulant therapy.…”
Section: Qol and Cardiovascular Prognosis In Patients With Paroxysmal Afmentioning
confidence: 90%
“…Based on the results of a largescale controlled study in Japan, Europe, and the United States, 17,22) antiplatelet therapy recommended in the previous JCS guidelines was deleted. Furthermore, warfarin therapy for prevention of ischemic stroke/systemic thromboembolism in patients with non-valvular AF is expected to be about more than 60% in Europe and the United States, 23) and Japan, 24) although its effi cacy is infl uenced by the quality of anticoagulant control that it provides (management of PT-INR). 25,26) According to a report from the J-RHYTHM registry, anticoagulant therapy is administered in more than 80% of patients with nonvalvular AF.…”
Section: Ischemic Stroke/systemic Thromboembolism In Patients Withmentioning
confidence: 99%